Epigenetic-Mediated Antimicrobial Resistance: Host versus Pathogen Epigenetic Alterations - Jibran Sualeh Muhammad; Naveed Ahmed Khan; Sutherland K. Maciver; Ahmad M. Alharbi; Hasan Alfahemi; Ruqaiyyah Siddiqui (MDPI AG, 2022)
Since the discovery of antibiotics, humans have been benefiting from them by decreasing the morbidity and mortality associated with bacterial infections. However, in the past few decades, misuse of antibiotics has led to the emergence of bacterial infections resistant to multiple drugs, a significant health concern. Bacteria exposed to inappropriate levels of antibiotics lead to several genetic changes, enabling them to survive in the host and become more resistant. Despite the understanding and targeting of genetic-based biochemical changes in the bacteria, the increasing levels of antibiotic resistance are not under control. Many reports hint at the role of epigenetic modifications in the bacterial genome and host epigenetic reprogramming due to interaction with resistant pathogens. Epigenetic changes, such as the DNA-methylation-based regulation of bacterial mutation rates or bacteria-induced histone modification in human epithelial cells, facilitate its long-term survival. In this review article, epigenetic changes leading to the development of antibiotic resistance in clinically relevant bacteria are discussed. Additionally, recent lines of evidence focusing on human host epigenetic changes due to the human-pathogen interactions are presented. As genetic mechanisms cannot explain the transient nature of antimicrobial resistance, we believe that epigenetics may provide new frontiers in antimicrobial discovery.